Basketball players' perception of their coaches - Monroy Anton, A. J.; Saez Rodriguez, G. (Human Movement, 2011)
The aim of this study was to analyse Spanish women basketball players` perception of their coaches in order to discover whether this perception is different from those in other sports and which character traits are the most appreciated in the sport of basketball. Methods. We administered a questionnaire survey in December 2010 to a total of 65 Spanish national division basketball players, where they were asked to evaluate their coaches with a set of 10 adjectives, rating them on a Likert seven-point scale with 1 being the least favourable and 7 the most favourable. Results. The results find that the players have a generally positive opinion of their coaches` personal qualities, although there were some small differences in the evaluation of what might be called "professional" qualities, which were not as high. Traits such as honesty (6.01), friendliness (5.97) or self-confidence (5.43) had higher values than imagination (4.3), dynamism (4.9), intelligence (5.1) and other attributes which could relate more to technical aspects or methods of training. With regard to the totality of the scale, the mean was found to be 5.22, with the maximum value being 6.01 for honesty and the lowest for imagination at 4.3. None of the analysed adjectives received a negative rating by the players. Conclusions. This study finds that women basketball players have an overall good perception of their coaches, as based on the analysed sample. These results are very similar to previous findings in other sports. In addition, they rate "personal" features with a higher score than traits that could be considered "professional" and, therefore, be an opinion of job performance.